Production of erythrocyte autoantibodies in NZB mice is inhibited by CD4 antibodies. - Oliveira, G G (1994)
NZB mice spontaneously develop haemolytic anaemia as the result of production of erythrocyte autoantibodies. The mechanisms leading to breakdown in tolerance to erythrocyte autoantigens are unknown. Antibodies to CD4 have been successfully used to treat several murine models of autoimmune disease. In this study we injected NZB mice with non-depleting CD4 antibodies and were able to prevent and abrogate erythrocyte autoantibody production in young (Coombs' negative) and old (Coombs' positive) mice, respectively. Our data indicate the dependency of autoantibody production on CD4+ T cells. However, withdrawal of anti-CD4 antibodies resulted in the appearance of erythrocyte autoantibodies, showing that under these conditions we were unable to re-establish tolerance to autoantigens on erythrocytes using anti-CD4 treatment.